Health anxiety by proxy in women with severe health anxiety: A case control study. (December 2017) - Thorgaard, Mette Viller; Frostholm, Lisbeth; Walker, Lynn; Jensen, Jens Søndergaard; Morina, Butrin; Lindegaard, Hanne; Salomonsen, Lone; Rask, Charlotte Ulrikka
Highlights: Severe health anxiety is associated with negative illness perceptions. Mothers' health anxiety also involves health-related worries towards their child. Mothers with health anxiety are less satisfied with their child's doctor visits. Health anxiety by proxy may be an overlooked treatment target in mothers. Abstract: Health anxiety (HA) refers to excessive worries and anxiety about harbouring serious illness based on misinterpretation of bodily sensations or changes as signs of serious illness. Severe HA is associated with disability and high health care costs. However, the impact of parental HA on excessive concern with their children's health (health anxiety by proxy) is scantly investigated. The aim of this study is to investigate HA by proxy in mothers with severe HA. Fifty mothers with severe HA and two control groups were included, i.e. mothers with rheumatoid arthritis (N = 49) and healthy mothers (N = 51). All participants completed self-report questionnaires on their own HA and illness perceptions and on illness worries and illness behaviour related to their children. The results showed that mothers with severe HA reported significantly more negative illness perceptions and more HA on behalf of their child (i.e. by proxy) compared to both control groups. HA by proxy may be an overlooked treatment target in mothers with severe HA, and improving our understanding of this condition can have important preventive and clinical implications.